A case study of sugarcane straw removal from the soil: what are the implications for soil organic matter content? - Silva, Rakiely Martins da (2021)
Brazil is the largest sugarcane producer in the world. With the changes in sugarcane harvesting systems, there is an expressive amount of straw that is deposited on the soil, which can contribute to the increase of soil organic matter (MOS). However, in Brazil there are already several Industrial Units that process all the sugarcane biomass to produce second generation alcohol and/or generate electricity, thus becoming a new source of income for the Plants and Distilleries. By processing all the biomass generated by sugarcane, the possible favorable effects on the chemical, physical and biological properties of the soil will be delayed. It is worth noting that organic matter determines the main attributes that define soil quality, being directly affected by management practices. Through the study of the quality of organic matter, it is possible, in addition to evaluating the quality of the soil, to have a greater understanding of the production system that this soil comprises. Given the above, the objective of this work was to study the main effects of removing straw from the soil surface on the organic matter content of the soil, indicating studies that indicate the ideal amount of straw to be left in the soil, without affecting the soil. organic matter content. For this, an intense search was carried out in databases, for studies that evaluated the possible implications of the total and partial removal of cane straw.